Prediction of Enhancer RNAs in Chicken Genome - Grushina, Valentina A.; Gagarina, Valeria S.; Prasolov, Danila E.; Kolpakov, Fedor A.; Gusev, Oleg A.; Pintus, Sergey S. (International journal of molecular sciences, 2025)
Enhancer RNAs (eRNAs) play an important role in transcriptional regulation and serve as key intermediates linking genomic enhancers to their target genes. Although ongoing efforts aim to annotate enhancers in the chicken genome, the current understanding of avian enhancers remains less developed compared to that of mammals. We utilized CAGE-seq data from chicken tissues obtained through the “Genetic Technologies in Poultry” project to predict enhancers in the chicken genome. Preliminary predictions focused on non-coding regions exhibiting bidirectional transcription, which were subsequently validated using explicit Markov models and refined with hidden Markov models. To assess sequence family homogeneity, we developed a method based on Euclidean distances between explicit Markov model matrices. Our analysis revealed that the proportion of enhancer-associated DNA in chicken is approximately similar to that observed in mammals, encompassing 9.29% of the entire chicken genome, roughly similar to the estimate made by the ChickenGTEx project. A relatively small number of them (12,242 enhancers) were significantly expressed among all tissues. Notably, more than half of the enhancer DNA overlapped intronic regions. Additionally, based on the bimodal distribution of enhancer lengths combined with the homogeneity of their Markov models, we identified a class of long enhancer elements which we hypothesize to be absent in mammals.